A Costume for Love to the Small Motherland - Lidin, Konstantin; Ushkova, Natalia (project baikal, 2014)
The territorial self-identification is based on the historical and geographical uniqueness of the place. The specific landscape where a city lives and develops is reflected in the aesthetic criteria of the regional culture. As a result, every element of the regional traditional culture is ‘image-balanced’ with the local landscape and can be considered as a bearer of a unique image of the place. This tendency is largely demonstrated in the regional traditional (folk) costume. The article shows an image-bearing connection between a folk costume and features of the landscape, climate, vegetation, etc. through the example of several regions in Bulgaria. The authors propose a general plan to highlight a unique image of Irkutsk and to capture it as a city brand-book.
Keywords: territorial identification; landscape; scenery; folk costume; cultural geography; Bulgaria